2016
DOI: 10.3390/nu8090536
|View full text |Cite
|
Sign up to set email alerts
|

Gender- and Age-Specific REE and REE/FFM Distributions in Healthy Chinese Adults

Abstract: Basic data on the resting energy expenditure (REE) of healthy populations are currently rare, especially for developing countries. The aims of the present study were to describe gender- and age-specific REE distributions and to evaluate the relationships among glycolipid metabolism, eating behaviors, and REE in healthy Chinese adults. This cross-sectional survey included 540 subjects (343 women and 197 men, 20–79 years old). REE was measured by indirect calorimetry and expressed as kcal/day/kg total body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
2
0
2
Order By: Relevance
“…It is possible that the effect of gender on REE/FFM is age-dependent in children and adolescents. In this sense, age has been considered a clear determinant of REE being negatively correlated in adults [ 65 ] mostly due to the changes in body composition [ 66 ], and positively in children and adolescents due to the age-related increase in body size [ 67 , 68 ]. In the present study, REE showed a moderate positive correlation with age, while REE/FFM was negatively correlated with age, in agreement with previous studies [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the effect of gender on REE/FFM is age-dependent in children and adolescents. In this sense, age has been considered a clear determinant of REE being negatively correlated in adults [ 65 ] mostly due to the changes in body composition [ 66 ], and positively in children and adolescents due to the age-related increase in body size [ 67 , 68 ]. In the present study, REE showed a moderate positive correlation with age, while REE/FFM was negatively correlated with age, in agreement with previous studies [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, the metabolic rate decreases with increasing age. However, while the influence of age on EE has been studied in a large healthy population [ 16 18 ], publications on measured EE in the critically ill mostly included a relatively small subgroup of elderly patients. Furthermore, the epidemics of obesity may complicate the application of prediction equations [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estudos têm mostrado diferenças no GER entre homens e mulheres (BYRNE et al, 2005;DIONNE et al, 1999;HENRY, 2005 (CHENG et al, 2016;GEISLER et al, 2016b;MCMURRAY et al, 2014;SIERVO et al, 2015; (GALLAGHER et al, 2006;SONG et al, 2016). Além disso, mulheres afro-americanas têm similares ou menores quantidades de gordura corporal total (GALLAGHER et al, 1996) e maiores quantidades de TO e TME (ORTIZ et al, 1992) A base teórica que sustenta a estratégia da relativização ocorreu devido os semelhantes resultados encontrados neste estudo com a literatura, como por exemplo, o TA representou 23,6% e 39,6% do peso corporal e uma influência de 4,8% e 9,3% no GER para homens e mulheres, respectivamente (Figuras 8a e b).…”
Section: Estimativa Do Gasto Energético De Repouso Considerando Sexounclassified